Motivasi belajar siswa SMP dalam pembelajaran matematika pasca pandemi - Rina Silviani; Risma Amelia (IKIP Siliwangi, 2023)
This study aims to see students' learning motivation in post-pandemic mathematics learning. The method used in this study is descriptive qualitative. The subjects of this study were 20 respondents of class VIII students in one of the junior high schools in Cimahi city. Data collection uses a questionnaire on student learning motivation in mathematics learning which has 10 statements that have positive and negative values. With the following indicators of desire and desire to succeed; encouragement and need to learn; hopes and ideals of the future; awards in learning and interesting activities in learning. This statement is used to find out respondents' answers regarding student learning motivation in mathematics learning. The results of the study showed that students had good motivation judging from the average percentage of indicators, namely 66.1% and was included in the strong category.